Brand Image And Tuition Affect STABN Sriwijaya Students’ Decisions - Pringgondani (Enrichment : Journal of Management, 2022)
This study aims to determine: (1) effect of brand image and education costs on student decisions choosing Buddhist Business and Management major at STABN Sriwijaya; and (2) the influence of brand image and education costs on students' decisions choosing Buddhist Business and Management major at STABN Sriwijaya. This study investigates causality. The population of this study consisted of 76 students enrolled in the Buddhist Business and Management major in semesters 2, 4, and 6 of the 2021/2022 academic year. Using the formula given by Surakhmad (Akdon, 2005: 107), the sample size of 39 people was calculated with a margin of error of 5 percent. The sample was selected using the direct method, namely random sampling. Using multiple linear regression, a questionnaire with a Lickert scale was used to collect and analyze the data. The research findings show that (1) brand image influences students' decisions about the Buddhist Business and Management Study Program at STABN Sriwijaya, (2) education costs affect students' decisions about the Buddhist Business and Management Study Program at STABN Sriwijaya, and (3) both. brand image and education costs influence student decisions regarding the Buddhist Business and Management Study Program at STABN Sriwijaya.